2005
DOI: 10.1002/mrm.20637
|View full text |Cite
|
Sign up to set email alerts
|

New experimental setup for studying strictly noninvasively skeletal muscle function in rat using 1H‐magnetic resonance (MR) imaging and 31P‐MR spectroscopy

Abstract: Traditional setups for in situ MR investigation of skeletal muscle function in animals use invasive systems for muscle stimulation and force measurement. These systems require surgical preparation and therefore exclude repetitive investigations on the same animal. This article describes a new experimental setup allowing strictly noninvasive MR investigations of muscle function in contracting rat gastrocnemius muscle using MR has proven its ability to investigate skeletal muscle function in situ. 31 P-Magnetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 20 publications
3
39
0
Order By: Relevance
“…The non-invasive muscle stimulation method has been proven to stimulate solely the triceps surae muscle complex and not the antagonist muscles. In fact, Giannesini et al (2005) found in their study, using T 2 -weighted MR images, that Table 1. LCRs seemed to have slightly higher initial maximal twitch force and MRTD (n.s.).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The non-invasive muscle stimulation method has been proven to stimulate solely the triceps surae muscle complex and not the antagonist muscles. In fact, Giannesini et al (2005) found in their study, using T 2 -weighted MR images, that Table 1. LCRs seemed to have slightly higher initial maximal twitch force and MRTD (n.s.).…”
Section: Discussionmentioning
confidence: 96%
“…The non-invasive MRS investigation setup used in our study was modified from the protocol designed by Giannesini et al (Giannesini et al 2005). Rats were deprived of food for 2 h before measurements.…”
Section: P-mrs Measurements (I)mentioning
confidence: 99%
“…Anesthetized animals were placed supine in a home-built cradle especially designed for the strictly noninvasive functional investigation of the right gastrocnemius muscle. 7 This cradle integrates a hydraulic ergometer and two rod-shaped transcutaneous electrodes (located above the knee and under the heel, respectively) connected to an electrical stimulator (Stimulator I series; Hugo Sachs Elektronik, Harvard Apparatus). The foot was positioned on the ergometer pedal and the hindlimb was immobilized in the cradle so that the lower hindlimb was centered inside a 30-mm-diameter 1 H Helmholtz imaging coil and the belly of the gastrocnemius muscle was located above an elliptic (10 Â 16 mm) 31 P-MRS surface coil.…”
Section: Chronic Effects Of Capsiate Administration B Faraut Et Almentioning
confidence: 99%
“…We used an original experimental setup allowing muscle function to be assessed strictly noninvasively in situ using magnetic resonance (MR) techniques and mechanical performance measurements. 7 The corresponding results were analyzed together with measurements of wholebody fat composition using magnetic resonance imaging (MRI) and changes in UCP3 gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…In order to rule out any methodological bias, we chose to use experimental conditions i.e., muscle length, number of contractions, contraction duration, whole exercise duration (Aldayel et al, 2010a,b;Jubeau et al, 2008) and stimulated muscle (Mackey et al, 2008) as close as possible to those previously used in humans. Additionally, rat muscle function was originally assessed by a strictly non-invasive experimental setup (Giannesini et al, 2005) offering the possibility to get, under physiological conditions in vivo, information about muscle mechanical performance (i.e., maximal tetanic force), anatomy (i.e., muscle volume) and physiology (i.e., T 2 changes) in contracting muscle and to repeat these investigations several times in the same animal, thereby allowing the first multimodal follow-up study of muscle injury after NMESinduced isometric contractions in rats. We hypothesized that, under comparable experimental conditions and in the absence of species-related differences in the magnitude of muscle injury, NMES of rat gastrocnemius muscles should result in an increased CK activity and T 2 values and a decreased tetanic force as previously reported in humans (Aldayel et al, 2010a,b;Jubeau et al, 2008).…”
Section: Introductionmentioning
confidence: 99%